2006
DOI: 10.2135/cropsci2006.01.0013
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic Variation for Stem Reserves and Mobilization in Wheat: II. Postanthesis Changes in Internode Water‐Soluble Carbohydrates

Abstract: Grain filling in wheat crops grown in semiarid regions may depend more on stored water-soluble carbohydrates (WSC) than on current photosynthesis. We evaluated the hypothesis that internode WSC content, specific content (WSC content/internode length), and concentration (WSC content/internode weight) of genotypes affect accumulation and mobilization of stem WSC. Genotypic variation for internode WSC-related traits was measured on the main stem at 10-d intervals in 11 diverse wheats grown under well-watered and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
91
0
17

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(117 citation statements)
references
References 29 publications
(56 reference statements)
9
91
0
17
Order By: Relevance
“…The amount of WSC in shoots was also highly correlated to the plant height. This agrees with previous works suggesting that stem reserve potential is determined by both stem length and stem specific weight (stem weight/stem length) (Blum, 1998;Ehdaie et al, 2006;Talukder et al, 2013). The coefficient of determination for the relationship between WSC and plant height was lower under EH than in other environments.…”
Section: Physiological Basis Of Heat Adaptationsupporting
confidence: 92%
“…The amount of WSC in shoots was also highly correlated to the plant height. This agrees with previous works suggesting that stem reserve potential is determined by both stem length and stem specific weight (stem weight/stem length) (Blum, 1998;Ehdaie et al, 2006;Talukder et al, 2013). The coefficient of determination for the relationship between WSC and plant height was lower under EH than in other environments.…”
Section: Physiological Basis Of Heat Adaptationsupporting
confidence: 92%
“…terminal drought) conditions and reported that the stem of rain fed wheat had higher fructan concentration than that of the irrigated stems. By contrast, in a study in which 11 wheat genotypes were subjected to post-anthesis DS, Ehdaie et al (2006b) reported that DS reduced the WSC content in the different internodes, except in the peduncle. All these results suggest that changes in WSCs under DS can greatly differ among wheat cultivars and stem parts.…”
Section: Discussionmentioning
confidence: 85%
“…There are two factors determining the magnitude of the stem reserves contributing to the grain yield; namely the ability of the stem to store photosynthate and the efficiency of remobilization and transport to the grain of the stored carbohydrates reserves. Stem reserves are important carbon sources for grain filling in crop plants, especially under adverse growing conditions (Ehdaie et al 2006, Fenta et al 2012). In the present study, WS treatments constrained current photosynthate accumulation in the stem (Fig 2), but stimulated the apparent remobilization of the stem reserves to the grain (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In cereals, grain-filling rate depends on the availability of current photoassimilate supply and the capacity of remobilizing carbohydrate reserves from the vegetative organs to the grains. The latter has been considered one major compensation mechanism to maintain a steady rate of grain filling when the current photosynthate supply is limited under abiotic stresses (Ehdaie et al 2006). Studies have shown that the remobilized reserves could contribute to 5-20 % of the final grain yield under non-stress conditions, while it might rise to 40-60 % under stressful growing conditions (Blum 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation